Teoría y práctica de la lingüística del discurso: "Análisis de textos en español" de Carmen Marimón - Garrido, Joaquín (Círculo de Lingüística Aplicada a la Comunicación, 2013)
Theory and practice of discourse linguistics. C. Marimon’s Spanish text analysis takes a practical approach to coherence and cohesion, based on an insightful review of current discourse linguistics theory. Key words: discourse linguistics, text coherence, text cohesion, Carmen Marimon.